PHYSICAL ACTIVITY IN FREE TIME OF YOUNG PEOPLE IN MONTENEGRO - Nela Tatar (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
The creation of positive attitudes and opinions of students toward physical education is one of the tasks of enduring value and should be achieved through teaching in physical education. Achievement of this objective is achieved by the enduring value and attitude to deal with the activities in the field of physical education. Given the importance of physical education as a subject or a part of education in the upbringing of the younger generation, cannot but emphasize its importance and impact on the ability of proper awareness of health, physical, mental and functional abilities, and even influence the formation of attitudes and interests of physical Education.The aim of this study is to determine whether there is an awareness of the importance of the school population movement and physical activity, you practice sports or recreational activities in their spare time or amount of exercise they meet in class, and if there is and how much interest to add additional hours of physical education in the form of compulsory or optional. Also how young people of different regions involved in sports and that, and that is to evaluate what their perception is sports.Data on data obtained during field research. The questionnaire consisted of three parts. The first part included demographic characteristics of the patients, other sports and physical activities, and the third part which relates to the subjective assessment of students on the importance of physical activity and the equipment room for the same. It is important to note that the data processing is done in such a summary and sex, municipality, region... As such; the data give us the possibility of regional and other comparisons ninth grade students in Montenegro.